The Reforms of 2009 to the Statute of the Inter-American Court of Human Rights: Regulation of Existing Practices and an Adjustment to the November 2000 Statute - Galvis Patiño, María Clara (2009)
In San José, Costa Rica, from January 19 to 31, 2009, the Inter-American Court of Human Rights held its eighty-second regular session, held at its headquarters "the Inter-American Court". There, a series of punctual reforms of the Statute of the Inter-American Court of Human Rights that came into force on March 24, 2009 were approved. Based on this, the article, first, raises the background and context in which it had the recent reform of the Statute of the Court. Then it is mentioned some of its issues and highlights, which have to do, on the one hand, with the Statute of practices that the Inter-American High Court has been adopting in recent years and, on the other, with the adjustment of specific aspects of the processing of the cases contained in the Statute adopted in November 2000, which came into force on June 1, 2013. Regarding this, the author emphasizes highlighting the evolution of the rules of procedure of the Inter-American Court in at least in two senses: on the one hand, to expedite and efficiently process and resolve cases; and, on the other, towards the strengthening of people's capacity to act autonomously as true parties during inter-American processes. Finally, the author will refer to pending issues that should be addressed in future reforms of the Court's Statute. For example, it is pending to go one step further to grant the victim the ius standi as a true plaintiff before the Court. In conclusion, the reform of January 29, 2009, as illustrated, does not contain major changes or radical modifications that imply a substantial alteration of the procedural stages or essential procedural faculties of the victims, the States and the IACHR; it is, on the one hand, to give regulatory consecration to existing practices, which had been well received by the parties; and, on the other hand, to make specific adjustments to certain aspects of the reforms of 2000 and 2003 that had been shown to affect the procedural balance or the agility of the procedure, either because they were unnecessary or because they did not favor procedural speed.